FINANCIAL ANALYSIS ON AGROFORESTRY SYSTEM OF COFFEE WITH MARRANGO TREE (Azadirachta excelsa Jack.) IN REJANG LEBONG REGENCY, BENGKULU PROVINCE, INDONESIA - Bambang Tejo Premono; Sri Lestari (Indonesian Journal of Forestry Research, 2018)
Marrango tree (Azadirachta excelsa Jack.) has been introduced as a shade tree for coffee plantations that also produces valuable timber for construction and energy. This paper analyzed the financial aspect of an agroforestry system of marrango tree and coffee plantations, including observations of land management, costs and revenues, financial feasibility and sensitivity analysis. The study was conducted in Rejang Lebong Regency, Bengkulu Province through field observations and interviews. Data was collected through direct observations, household surveys and in-depth interviews of several key actors to deepen the information and verify the collected data. Descriptive quantitative and financial analyses were employed to analyze the data. The results showed that the land management of marrango tree and coffee plant agroforestry in Rejang Lebong Regency was conducted in the traditional way. However, the agroforestry system of coffee plants and marrango tree was financially feasible at the level of 8% discounted rate (NPV = 76,250,582 IDR; BCR = 2.28 and IRR = 22%). This agroforestry system also has good resistance to changes in coffee price, coffee production and marrango tree price. The agroforestry system remained feasible although if coffee production declined by 50%, coffee price decreased up to 40%, and timber production declined up to 50%.  The changes in coffee production and price were the most influential factors on the feasibility of the agroforestry system. This agroforestry system is beneficial for the farmers. Hence, the local government should encourage the community to apply this system.